2020
DOI: 10.1002/bies.202000104
|View full text |Cite
|
Sign up to set email alerts
|

Speculating on the Roles of Nuclear Speckles: How RNA‐Protein Nuclear Assemblies Affect Gene Expression

Abstract: Nuclear speckles are eukaryotic nuclear bodies enriched in splicing factors. Their exact purpose has been a matter of debate. The different proposed roles of nuclear speckles are reviewed and an additional layer of function is put forward, suggesting that by accumulating splicing factors within them, nuclear speckles can buffer the nucleoplasmic levels of splicing factors available for splicing and thereby modulate splicing rates. These findings build on the already established model that nuclear speckles func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 153 publications
(184 reference statements)
1
14
0
Order By: Relevance
“…It is worth noting that besides SON, we are not ruling out the possibility that other nuclear speckle proteins and/or RNAs may also regulate the 12-hour nuclear speckle LLPS dynamics, with the Pickering agent, which has recently been found to be regulating P granules coarsening, being a tantalizing candidate (41). Our results further reconcile the debate on the exact roles of nuclear speckles in gene regulation: whether the nuclear speckles mainly function as the "storage facility" of mRNA processing factors away from chromatin, or they can actively participate in gene regulation process via physical engagement with chromatin (42). We showed here that nuclear speckles can function as both, but these two functions are probably temporally separated because of the oscillation of SON expression and the according changes in their LLPS dynamics and propensity to associate with chromatin.…”
Section: Discussionsupporting
confidence: 79%
“…It is worth noting that besides SON, we are not ruling out the possibility that other nuclear speckle proteins and/or RNAs may also regulate the 12-hour nuclear speckle LLPS dynamics, with the Pickering agent, which has recently been found to be regulating P granules coarsening, being a tantalizing candidate (41). Our results further reconcile the debate on the exact roles of nuclear speckles in gene regulation: whether the nuclear speckles mainly function as the "storage facility" of mRNA processing factors away from chromatin, or they can actively participate in gene regulation process via physical engagement with chromatin (42). We showed here that nuclear speckles can function as both, but these two functions are probably temporally separated because of the oscillation of SON expression and the according changes in their LLPS dynamics and propensity to associate with chromatin.…”
Section: Discussionsupporting
confidence: 79%
“…Nuclear speckles provide storage for splicing factors with no or few post-translational 179 modifications. Nuclear speckles break down and reform as cells progress through mitosis 180 (Figure 2); this dynamic phenomenon was first shown to be dependent on SRPK1 in HeLa cells 181 [59,60,62,63] and later to be shared with its homologue SRPK2 in various human cells lines 182 and tissues [61]. SRPKs are more active during M phase, leading to nuclear speckle 183 disassembly by phosphorylating splicing factors [64].…”
Section: Phase 178mentioning
confidence: 99%
“…The sub‐localization of Pst_A23 in nuclear speckles, which is rich in splicing factors (Hasenson and Shav‐Tal, 2020 ), suggested that Pst_A23 may interfere with the host’s AS process. Hence, we sequenced the transcriptome of a transgenic plant line overexpressing Pst_A23 and compared it to that of WT wheat.…”
Section: Resultsmentioning
confidence: 99%